Fostering Knowledge Transfer through High- Performance HRM Practices: The Mediating Role of Affective Commitment - Ikyanyon, Darius N.; Ode, Egena (European Scientific Journal, ESJ, 2017)
Due to the importance of knowledge transfer in enhancing competitive advantage of firms, organizations are increasingly developing strategies for effective knowledge transfer. This study examined the relationship between high-performance HRM and knowledge transfer as well as the mediating effect of affective commitment on this relationship. The study is based on data from 136 mangers drawn from six banks in Nigeria. Through the use of regression analysis and mediation analysis using PROCESS macros, we report a positive relationship between highperformance HRM and knowledge transfer. We also found a positive relationship between affective commitment and knowledge transfer. In turn, affective commitment mediated the relationship between high-performance HRM and knowledge transfer. The study therefore concluded that highperformance HRM contributes to knowledge transfer directly and indirectly through affective commitment.